Do anti-carbamylated protein antibodies in rheumatoid arthritis reflect local and systemic osteoporosis? A study of osteoprotegrin and receptor activator for nuclear factor kappa B ligand and radiological assessment - Manal Shawky Hussein; Rasha Ahmed Gaber; Hala Mostafa Elsabagh; Elsayed Mohamed Rageh (Egyptian Rheumatology and Rehabilitation, 2021)
Abstract Background One of the most important and dangerous complications of rheumatoid arthritis (RA) is bone loss, which manifested by erosions and juxta-articular or systemic bone loss. Anti-carbamylated protein (anti-CarP) antibodies which are also called anti-homocitrulline antibodies have recently been found in RA. Increase anti-CarP antibody titres may lead to severe disease and increase the progression of bone loss. Osteoprotegrin and receptor activator for nuclear factor kappa B and its ligand (RANKL) are the main players in the pathogenesis of osteoporosis. Thus, we aimed to investigate and detect the presence and prevalence of anti-CarP in rheumatoid arthritis and their association with disease severity and osteoporosis, as well as with OPG/RANKL in 80 Egyptian RA patients to highlight this relationship which could be useful in managing RA patients with osteoporosis. Results Serum anti-CarP levels were significantly increased in the RA group compared with the control group (P< 0.001). We found a negative association between anti-CarP and anti-CCP and disease activity (r=−0.878, −0.534, respectively, P<0.001). We also found a positive correlation between anti-CarP and the Larsen score, DEXA score, RF, HAQ, and RANKL (r=0.646, 0.287, 0.243, 0.892, 0.671, 0.869 [respectively], P<0.001) and there was negative correlation between anti-CarP and OPG (r=−0.553, P<0.001). Conclusion Anti-CarP antibodies are associated with disease severity and disability in RA patients. They could play an important and significant role in the pathogenesis of osteoporosis in these patients.